The Georgia Colony - Fradin, Dennis B. (Chicago, Ill. : Childrens Press, 1990)
This book gives a historical account of Georgia's early days, from its creation as a colony for debtors in the 1700s until its admission as the fourth state in 1788.
Includes index.
Keywords: Georgia -- History